Imaging and histopathologic characteristics of typical pancreatic hamartoma: a case report and literature review - Liu, Shunli; Yang, Lei; Wu, Jie; Lin, Xin; Zhang, Zaixian (Frontiers in Oncology, 2024)
Background: Pancreatic hamartoma, a rare benign non-neoplastic condition, presents challenges in differentiating from other pancreatic diseases due to its atypical imaging and unreliable biopsy results. In this study, we present a case of pancreatic hamartoma and conduct a comprehensive review of relevant literature to outline its characteristic features, aiming to underscore its clinical relevance and implications. Case presentation: A 63-year-old man presented with a pancreatic mass, discovered during evaluation of abdominal pain and distension. Laboratory tests were largely unremarkable. Ultrasound revealed a hypoechoic mass in the head of the pancreas. Subsequent computed tomography and magnetic resonance imaging demonstrated an inhomogeneous mass with a clear boundary in the uncinate process of the pancreas. Furthermore, a distinct delayed enhancement pattern was noted on imaging. Histopathological examination confirmed the diagnosis of pancreatic hamartoma. Conclusion: Preoperative diagnosis of pancreatic hamartoma remains challenging. Imaging modalities can play a crucial role in facilitating accurate diagnosis and potentially avoiding unnecessary surgical intervention in patients with this condition.